Mediterranean Diet and Micronutrient Adequacy in Relation to Relapsing‐Remitting Multiple Sclerosis Risk: A Case‐Control Study - Maryam Ahmadi‐Khorram; Alireza Hatami; Mostafa Shahraki Jazinaki; Yasaman Aali; Maedeh Nojoumi; Fatemeh Keykhaei; Ali Jafarzadeh Esfehani; Mohsen Nematy (Health Science Reports, 2026)
ABSTRACT Background Multiple sclerosis (MS) is a chronic autoimmune and neurodegenerative disease influenced by environmental factors, including diet. The Mediterranean Diet (MeDi), rich in anti‐inflammatory and antioxidant compounds, and micronutrient adequacy may reduce MS risk and progression. Aim This study aims to examine the associations between the Mediterranean Diet Score (MDS), Mean Adequacy Ratio (MAR), and MS risk in a case‐control setting. Methods This case‐control study included 197 newly diagnosed relapsing‐remitting MS patients (aged 18–65 years) from Iran, and 200 matched controls without neurological diseases. Dietary intake was assessed using a validated semi‐quantitative food frequency questionnaire. MDS was calculated based on nine dietary components, and MAR was computed as the average Nutrient Adequacy Ratio for seven micronutrients. Adjusted binary logistic regression estimated odds ratios (ORs) for MS risk across MDS and MAR tertiles. Results Higher MDS and MAR were associated with significantly reduced MS risk. Individuals in the highest MDS tertile had 47% lower odds of MS (OR: 0.53, 95% CI: 0.29–0.98, p = 0.04), and those in the highest MAR tertile had 75% lower odds (OR: 0.25, 95% CI: 0.10–0.62, p = 0.002) compared to the lowest tertiles after adjustments. No significant differences in total energy or macronutrient intake were observed between groups. Conclusion Higher adherence to the Mediterranean Diet and better micronutrient adequacy are associated with a reduced risk of MS. These findings highlight the potential of dietary interventions as a cost‐effective strategy for MS prevention, warranting further longitudinal and interventional studies to establish causality and inform public health strategies. Trial Registration: The Mashhad University of Medical Sciences approved the study with numbers IR.MUMS.REC.1393.182.